Redesain dan Analisa Kekuatan Rangka Mesin Uji Tarik Kapasitas 5 Ton - Rudian Fenda Ramadhani; Ali Akbar; Yasinta Sindy Pramesti (Prosiding Seminar Nasional Ilmu Teknik, 2026)
This study aims to redesign the frame of a 5-ton tensile test device by adding wheels to the lower mount without reducing the loading capability. The design was carried out to increase the mobility of laboratory equipment while ensuring that the strength and safety aspects of the structure are maintained. The structural strength analysis was carried out using SolidWorks Simulation based on Finite Element Analysis (FEA) with ST 37 steel material and a static load of 50,000 N. The main parameters analyzed included Von Mises voltage, displacement, and factor of safety. The simulation results showed a maximum Von Mises voltage of 86.149 MPa, a maximum displacement of 0.073 mm, and a minimum safety factor of 2.72. The stress value is still below the ST 37 steel melt stress, so the structure works on an elastic area without causing permanent deformation. These findings confirm that the redesigned frame is feasible to use because it meets the structural strength, rigidity, and safety requirements. This research makes a practical contribution to the development of laboratory equipment that is more efficient, safe, and easy to move, and can be a reference for further research in structural design based on numerical simulations.